Phyto-Mediated Copper Oxide Nanoparticles for Antibacterial, Antioxidant and Photocatalytic Performances - Ssekatawa, Kenneth; Byarugaba, Denis K.; Angwe, Martin Kamilo; Wampande, Eddie M.; Ejobi, Francis; Nxumalo, Edward; Maaza, Malik; Sackey, Juliet; Kirabira, John Baptist (Frontiers in Bioengineering and Biotechnology, 2022)
The greatest challenge of the current generation and generations to come is antimicrobial resistance, as different pathogenic bacteria have continuously evolved to become resistant to even the most recently synthesized antibiotics such as carbapenems. Resistance to carbapenems limits the therapeutic options of MDR infections as they are the only safe and effective drugs recommended to treat such infections. This scenario has complicated treatment outcomes, even to the commonest bacterial infections. Repeated attempts to develop other approaches have been made. The most promising novel therapeutic option is the use of nanomaterials as antimicrobial agents. Thus, this study examined the efficacy of Camellia sinensis extract (CSE) and Prunus africana bark extract (PAE) green synthesized Copper oxide nanoparticles (CuONPs) against carbapenem-resistant bacteria. Furthermore, the photocatalytic and antioxidant activities of CuONPs were evaluated to determine the potential of using them in a wide range of applications. CuONPs were biosynthesized by CSE and PAE. UV vis spectroscopy, X-ray Diffraction (XRD), Dynamic light scattering (DLS), Fourier Transform Infrared spectroscopy (FTIR), and Scanning Electron Microscopy (SEM) were used to characterize the nanoparticles. CuONPs susceptibility tests were carried out by the agar well diffusion method. The photocatalytic and antioxidant activities of the CuONPs were determined by the methylene blue and DPPH free radical scavenging assays, respectively. UV vis absorbance spectra registered surface plasmon resonance peaks between 272 and 286 nm, confirming the presence of CuONPs. The XRD array had nine strong peaks at 2θ values typical of CuONPs. FTIR spectra exhibited bands associated with organic functional groups confirming capping and functionalization of the CuONPs by the phytochemicals. DLS analysis registered a net zeta potential of +12.5 mV. SEM analysis revealed that the nanoparticles were spherical and clustered with a mean diameter of 6 nm. Phytosynthesized CuONPs exhibited the highest growth suppression zones of 30 mm with MIC ranging from 30 to 125 µg/mL against MDR bacteria. Furthermore, the CuONPs achieved a methylene blue dye photocatalysis degradation efficiency of 85.5% and a free radical scavenging activity of 28.8%. PAE and CSE successfully bio-reduced copper ions to the nanoscale level with potent antimicrobial, photocatalysis, and antioxidant activities.